PENGEMBANGAN MEDIA ULAR TANGGA BERBASIS SCRATCH UNTUK LITERASI MITIGASI BANJIR ROB BAGI SISWA SD - Paramita, Arzety Putri; Wahyuningsih, Yona; Nanggala, Agil (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
Indonesia's coastal areas periodically face the threat of tidal flooding, which has a significant impact on community activities, including elementary school students who are classified as a disaster-prone group. Low disaster mitigation literacy, especially related to tidal flooding, and the lack of contextual and interactive learning media are major problems in disaster education in elementary schools. This study aims to develop Scratch-based digital snakes and ladders learning media integrated with tidal flood mitigation literacy material for fifth-grade elementary school students in coastal areas. The research method uses a Design and Development (D&D) approach with a 4D model limited to the develop stage, including define, design, and develop. The mitigation content was compiled based on the IPAS curriculum and national disaster preparedness guidelines, covering the pre-, during, and post-tidal flooding phases, and was designed to measure higher-order cognitive abilities (C4–C6). The results showed that the developed media was able to systematically integrate tidal flood mitigation material into an interactive and competitive game flow, equipped with an instant feedback mechanism through the Scratch algorithm. This media was considered to have the potential to help students understand the concept of mitigation in a more concrete, contextual, and meaningful way.